Public Cemetery’s Potency as The Source of Proteolytic Bacteria - Rika Dini Saputri; Erma Musbita Tyastuti; Yasir Sidiq; Triastuti Rahayu (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2023)
Cemetery is an area provided for burial and acts as an active bodies disposal site. One group of bacteria which is likely to be found with a high population is the proteolytic bacteria because the human body is made up of 46.85% protein. The exploration of proteolytic bacteria from public cemetery in Indonesia has not been conducted as so this research is necessary and become the main objective of this study. This research is a non-experimental study to isolate soil bacteria from Pracimaloyo public cemetery in the district of Kartasura. Skim Milk Agar (SMA) is used as selective media. Proteolytic capacity was determined using the proteolytic index (PI). Potential proteolytic bacteria isolates were identified based on morphology features and PI values > 2 were isolated from P23 and P22 isolates. Bacterial proteolytic isolates are dominantly colonies of white to yellowish with irregular and circular shapes. Gram-staining results indicated that bacterial isolates with proteolytic abilities are belong to Gram-negative bacili bacteria. The highest PI value of bacterial isolates exhibited by P23 isolates and possibly belong to the genus Bacillus. The study has discovered that Pracimaloyo holds the potential as a proteolytic soil bacteria habitat dominated by the Gram-negative group.